Analysis of the use of methods for the calculation and collection of taxes on personal income in Russia and Kazakhstan - Ischuk, T.L.; Baimukhametova , A.S. (BUKETOV BUSINESS REVIEW, 2018)
In the article methods of calculation and collection of taxes from incomes of individuals both in Kazakhstan and in Russia are considered, and also a comparative analysis of their application is made. Such methods of calculating taxes as cumulative and non-cumulative as well as in the form of a fixed interest rate to the price of selling goods (work, services), solid absolute amounts from a unit of the object, by multiplying the interest rate on the taxable base, as well as the areas of their application both in Kazakhstan and in Russia. In addition, the methods of tax collection on the basis of the declaration (or the method of self-assessment), the method of withholding (the method of withdrawal of the tax until the entity receives income, or the method called at the source of payment), the cadastre method (based on tax notice), the method of withdrawal at the time of income expenditure , an administrative way, by self-calculation and making a tax payment, as well as their advantages and disadvantages. It is determined that the largest share of tax revenues by IDPs in Kazakhstan and personal income tax in Russia in terms of methods for calculating and levying taxes is accounted for by the income tax, the source of which is the tax agent, that is, the source of payment. Also, the use of different methods for calculating the personal income tax in Russia and Kazakhstan is associated with different tax periods for the taxes in question. Other conclusions were also drawn.